SYSTEM OF FINANCING PYMES-LIMA METROPOLITAN GRAPHICS INDUSTRY SECTOR - Barrón Araoz, Ricardo Ampelio (2011)
Graphics industry sector, in Metropolitan Lima has experienced spectacular growth, both micro, small, medium and large business, developing various products of potential demand. In the last two decades, Peru experienced amazing changes, the nation's political system, as it implemented the system of regionalization, that these divisions autonomously manage their natural resources, on the other hand, private universities are created under the under Legislative Decree 882, Law of Educational Development, or for profit. These changes, users create more diversity of products in the printing industry, which, given the increase in demand, also require higher production volumes and sales, and for this major funding sources. The printing industry of companies, like many other parts of Peru, characterized by the presence of formal firms to a lesser extent, while the large proportion is in informal conditions. The research purpose was to determine the system of financing of these companies to generate their output, taking into account the forms of financing are own resources or borrowed funds, as loans, credits, overdrafts, hire purchase, leasing system, the latter used in Europe and Asia, with great advantages for the acquisition of sophisticated machinery for the printing industry purpose. The study was conducted only in the area of Lima. In addition concern was to discover our approximate number of formal and informal enterprises, so that the latter conform to the law and access to financing.